Assessment of Active Vertical Carbon Transport: New Methodology - L.E. Kwong; E.A. Pakhomov (Учёные записки Казанского университета: Серия Естественные науки)
Estimating active carbon transport in aquatic ecosystems has proven to be a labor-intensive and time-consuming process. This study proposes a novel approach to assess active carbon transport of zooplankton and micronekton based on the biomass spectra theory. This method is unique, as compared to the previous studies, because it relies solely on organism size rather than taxonomy. To predict active carbon transport, we use abundance size spectra during the day and night in the epipelagic zone, binned into log-2 size bins, which can then be used to calculate nominal size class and total abundance for each size bin. These calculations are applied to pre-existing size-dependent rate equations for respiration, excretion, mortality and gut flux, along with system temperature, time spent at depth, and depth of vertical migration. In combination with optical and acoustic methods, we hope that this method will shed light on the vast contribution of zooplankton and micronekton to global carbon export, and encourage the inclusion of active carbon transport estimates into global biogeochemical models. This will aid better understanding of the climate change implications to the global carbon cycling.